1993
DOI: 10.1021/om00035a068
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of cyclopalladated N,N-dimethylbenzylamine complexes by inorganic and organic peroxides: oxygen insertion into the palladium-carbon bond

Abstract: Little is known about the reactivity of d8 organometallic complexes with either organic or inorganic peroxo species as electrophiles. It is remarkable that, despite the current interest in the chemistry of late-transition-metal alkoxides and phenoxides,2 a preparative method based on oxygen insertion into the metal-carbon bond of organometallic compounds has so far remained unexplored. The search for selective methods for the oxy-functionalization of hydrocarbons3 provides a stimulus for the study of this subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 0 publications
3
69
0
Order By: Relevance
“…The beneficial effect of protic solvents (tBuOH) in the metaloxylation of organopalladium complexes with TBHP has been reported. [17] Formation of alcohol oxide species (RHO-O) in protic solvents was believed to be the actual oxygen-donating agent in oxygentransfer reactions by TBHP because the RHO-O species can provide an oxenoid oxygen atom and a neutral leaving group. [17] It is tempting to believe that TBHP reacts directly with (L sal )Ni to afford (OL sal )Ni, following a concerted one-step mechanism via formation of intermediate I-B as shown in Scheme 3.…”
Section: Synthesis Of (Ol Sal )Ni From (L Sal )Nimentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of protic solvents (tBuOH) in the metaloxylation of organopalladium complexes with TBHP has been reported. [17] Formation of alcohol oxide species (RHO-O) in protic solvents was believed to be the actual oxygen-donating agent in oxygentransfer reactions by TBHP because the RHO-O species can provide an oxenoid oxygen atom and a neutral leaving group. [17] It is tempting to believe that TBHP reacts directly with (L sal )Ni to afford (OL sal )Ni, following a concerted one-step mechanism via formation of intermediate I-B as shown in Scheme 3.…”
Section: Synthesis Of (Ol Sal )Ni From (L Sal )Nimentioning
confidence: 99%
“…[17] Formation of alcohol oxide species (RHO-O) in protic solvents was believed to be the actual oxygen-donating agent in oxygentransfer reactions by TBHP because the RHO-O species can provide an oxenoid oxygen atom and a neutral leaving group. [17] It is tempting to believe that TBHP reacts directly with (L sal )Ni to afford (OL sal )Ni, following a concerted one-step mechanism via formation of intermediate I-B as shown in Scheme 3. Nevertheless, formation of a (L sal ) Ni IV =O intermediate [18] can not be excluded unequivocally though it is expected to be unstable for Ni IV (d n oxo system, n ÏŸ 4), [19,7d] and a doubly bonded Ni IV =O species is unlikely to be involved since it is better represented as either Ni III -O· or Ni IV -O -.…”
Section: Synthesis Of (Ol Sal )Ni From (L Sal )Nimentioning
confidence: 99%
“…For example, Brown and Mayer have reported a phenyl-to-oxo migration in [TpRe(O)(Ph)(OY)]- [OTf] (Y = SMe 2 or pyridine), which results in a net oxygen insertion into Re-R bonds under both thermal and photolytic conditions. [28,29] Oxygen atom insertion into Pd-aryl bonds has been reported, [30,31] and Hillhouse and coworkers have reported examples of Ni-alkyl-to-Ni-alkoxido transformations using N 2 O. [32][33][34][35] Abu-Omar and Espenson reported that the reaction of methyltrioxorhenium (MTO) with oxidants generates methanol, [36] and recently, Periana, Goddard, and co-workers reported a proposed mechanism for this reaction that proceeds by oxidant coordination and subsequent methyl migration to the coordinated oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the insertion of oxygen into palladium-aryl and nickel-aryl bonds is already known. [31][32][33] This class is more promising for integrating the OM-BV oxy-functionalization with alkane C-H activation, since late transition metals are known for activating alkane C-H bonds in oxidizing conditions. 11,34,35 Therefore, we will focus on those systems in the future.…”
Section: Discussionmentioning
confidence: 99%